Gut Microbiota Promote Angiotensin II–Induced Arterial Hypertension and Vascular Dysfunction. Issue 9 (September 2016) - Karbach, Susanne H.; Schönfelder, Tanja; Brandão, Ines; Wilms, Eivor; Hörmann, Nives; Jäckel, Sven; Schüler, Rebecca; Finger, Stefanie; Knorr, Maike; Lagrange, Jeremy; Brandt, Moritz; Waisman, Ari; et al.
Abstract : Background: The gut microbiome is essential for physiological host responses and development of immune functions. The impact of gut microbiota on blood pressure and systemic vascular function, processes that are determined by immune cell function, is unknown. Methods and Results: Unchallenged germ‐free mice (GF) had a dampened systemic T helper cell type 1 skewing compared to conventionally raised (CONV‐R) mice. Colonization of GF mice with regular gut microbiota induced lymphoid mRNA transcription of T‐box expression in T cells and resulted in mild endothelial dysfunction. Compared to CONV‐R mice, angiotensin II (AngII; 1 mg/kg per day for 7 days) infused GF mice showed reduced reactive oxygen species formation in the vasculature, attenuated vascular mRNA expression of monocyte chemoattractant protein 1 (MCP‐1), inducible nitric oxide synthase (iNOS) and NADPH oxidase subunit Nox2, as well as a reduced upregulation of retinoic‐acid receptor‐related orphan receptor gamma t (Rorγt), the signature transcription factor for interleukin (IL)‐17 synthesis. This resulted in an attenuated vascular leukocyte adhesion, less infiltration of Ly6G + neutrophils and Ly6C + monocytes into the aortic vessel wall, protection from kidney inflammation, as well as endothelial dysfunction and attenuation of blood pressure increase in response to AngII. Importantly, cardiac inflammation, fibrosis and systolic dysfunction were attenuated in GF mice, indicating systemic protection from cardiovascular inflammatory stress induced by AngII. Conclusion: Gut microbiota facilitate AngII‐induced vascular dysfunction and hypertension, at least in part, by supporting an MCP‐1/IL‐17 driven vascular immune cell infiltration and inflammation.